The Value of Values for Understanding Organizational Life: Editor's Introduction to the Lead Article. Issue 2 (2nd September 2019) - Stephan, Ute
Abstract : In this introduction to the lead article on "Values at Work", I summarize key points made in the lead article and its commentaries including those relating to the mechanisms and boundary conditions of value–behavior relationships. I highlight links with the organizational and management literature, which pays increasing attention to the role of values in organizations. I note that there are many synergies yet to be explored between, on the one hand, work on values traditionally rooted in social and cross‐cultural psychology and as represented by the lead article and commentaries and, on the other hand, management and organizational research. One example is research on the values of strategic leaders and considering values as decision‐making standards that can shape organizations and their management.